Study on CO2 gasification properties of coal gasification wastewater slurry. Issue 3 (28th January 2021) - Liu, Jianzhong; Li, Dedi; Wang, Jianbin; Chen, Zhi; Cheng, Jun; Cen, Kefa
Abstract: Coal water slurry technology and gasification technology are used to simultaneously treat wastewater and CO2 ; coal water slurry is prepared from fixed‐bed coal gasification wastewater; and then, thermogravimetric analysis, Fourier‐transform infrared spectrometry, scanning electron microscopy, energy‐dispersive spectrometry, and X‐ray diffraction are used to analyze the characteristic parameters of CO2 gasification and the products that formed. The results reveal the following: (a) compared with coal water slurry, coal gasification wastewater slurry shows decreases in the gasification start temperature, gasification weight loss peak temperature, and gasification end temperature of 12°C, 22°C, and 17°C, respectively, and shows increases in the maximum and average reaction rates. In addition, the reactivity index for coal gasification wastewater slurry is found to be 14.29% higher than that for ordinary coal water slurry. (b) Coal gasification wastewater slurry produces more methane and other aliphatic hydrocarbon gases in the pyrolysis stage and more CO in the coke gasification stage than coal water slurry. (c) Coal gasification wastewater slurry contains many small particles and flocs on the surface of the coal and a high Na content (up to 8.07%) in the microarea. In addition, a richer pore structure exists on the surface of the gasification residue of the coal gasification wastewater slurry. (d) The components of the gasification residue for coal gasification wastewater slurry show relatively larger changes. Moreover, the catalytic effect of alkali metal may be weakened due to the reaction of the minerals in the coal to form a complex.